Reformasi Pendidikan Islam dalam Kebijakan Pendidikan Era Reformasi: ISLAMIC EDUCATION REFORM IN EDUCATION POLICY IN THE REFORM ERA - Sulis, Sulistri; Khoiri, Qolbi (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to understand the rules made by the government during the reform era for Islamic Education. A rule that is already present can provide a problem so that it provides the need to solve it properly. Therefore, this rule can be used as a guideline. The purpose of this study is to be able to provide an explanation and develop educational policies in the reform era and explain the system and rules of the Indonesian Government in this reform era in the field of education, especially in Islamic education. This study uses a qualitative type with a phenomenological approach, informant selection techniques through purposive sampling and collecting data through interviews, observations, and documentation